1994
DOI: 10.1111/j.1365-2265.1994.tb02488.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperinsulinaemia on the function of the pituitary‐adrenal axis in healthy man

Abstract: The peak cortisol response to CRH was diminished at the higher circulating insulin levels. This was not dependent upon concurrent hypoglycaemia and did not appear to be mediated at the level of the pituitary gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the patient group, maximal cortisol levels also varied (from 334 to 718 nmol/L) and in some cases responses could be considered suboptimal (11). Obesity and hyperinsulinemia may attenuate the adrenocortical response to CRH (19); however, these factors are not present in these patients and the exact reason for the individual sub-responsiveness is not clear. Patients with DTC receive treatment with thyroxine in suppressive doses as part of their therapy (20) and consequently are subclinically or even clinically hyperthyroid.…”
Section: Discussionmentioning
confidence: 96%
“…In the patient group, maximal cortisol levels also varied (from 334 to 718 nmol/L) and in some cases responses could be considered suboptimal (11). Obesity and hyperinsulinemia may attenuate the adrenocortical response to CRH (19); however, these factors are not present in these patients and the exact reason for the individual sub-responsiveness is not clear. Patients with DTC receive treatment with thyroxine in suppressive doses as part of their therapy (20) and consequently are subclinically or even clinically hyperthyroid.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies investigated the role of mild to moderate hyperinsulinemia in the regulation of the HPA axis in vivo using the euglycemic hyperinsulinemic clamp technique (34,35). They reported disparate results, however, with one study demonstrating a diminished cortisol response to CRH in conditions of moderate hyperinsulinemia (34) and the other reporting an increase of ACTH and cortisol blood levels with increasing insulin levels during the clamp study, therefore suggesting a stimulatory effect of insulin on the HPA axis secretory capacity. No studies have investigated this issue in obese subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Short‐term studies using euglycaemic clamps have shown that hyperinsulinaemia causes activation of the HPA axis (Fruehwald‐Schultes et al ., , ). However, cortisol response to corticotrophin‐releasing hormone (CRH) is lower in those with higher circulating insulin levels (Walker et al ., ). Patients with insulinoma (who have persistent hyperinsulinaemia) also have poor cortisol response to hypoglycaemia (Grimaldi et al ., ; Chang et al ., ).…”
Section: Introductionmentioning
confidence: 97%